Pedagogical Value of Polling-Place Observation by Students. Issue 4 (16th May 2018) - Mann, Christopher B.; Alberda, Gayle A.; Birkhead, Nathaniel A.; Ouyang, Yu; Singer, Chloe; Stewart, Charles; Herron, Michael C.; Beaulieu, Emily; Boehmke, Frederick; Boston, Joshua; Cantu, Francisco; Cobb, Rachael; et al.
ABSTRACT: Good education requires student experiences that deliver lessons about practice as well as theory and that encourage students to work for the public good—especially in the operation of democratic institutions (Dewey 1923; Dewy 1938). We report on an evaluation of the pedagogical value of a research project involving 23 colleges and universities across the country. Faculty trained and supervised students who observed polling places in the 2016 General Election. Our findings indicate that this was a valuable learning experience in both the short and long terms. Students found their experiences to be valuable and reported learning generally and specifically related to course material. Postelection, they also felt more knowledgeable about election science topics, voting behavior, and research methods. Students reported interest in participating in similar research in the future, would recommend other students to do so, and expressed interest in more learning and research about the topics central to their experience. Our results suggest that participants appreciated the importance of elections and their study. Collectively, the participating students are engaged and efficacious—essential qualities of citizens in a democracy.